Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 187961 by normans last updated on 24/Feb/23

Answered by HeferH last updated on 24/Feb/23

Commented by HeferH last updated on 24/Feb/23

i. (R−3)^2  = 9 + (R^2 /4)   R^2 +9−6R = 9 + (R^2 /4)   4R^2 −24R = R^3    3R^2  = 24R   R = 8    ii. (R−r)^2 −r^2 = ((R/( (√2)))+r)^2 −((R/( (√2)))−r)^2    R^2 −2Rr= ((4Rr)/( 2))(√2)   R−2r= 2r(√2)   R = 2r + 2r(√2)   r = (R/(2 + 2(√2)))   r = (8/(2+2(√2))) = (4/(1+(√2))) = ((4((√2)−1))/(2−1)) = 4((√2)−1)

$${i}.\:\left({R}−\mathrm{3}\right)^{\mathrm{2}} \:=\:\mathrm{9}\:+\:\frac{{R}^{\mathrm{2}} }{\mathrm{4}} \\ $$$$\:{R}^{\mathrm{2}} +\mathrm{9}−\mathrm{6}{R}\:=\:\mathrm{9}\:+\:\frac{{R}^{\mathrm{2}} }{\mathrm{4}} \\ $$$$\:\mathrm{4}{R}^{\mathrm{2}} −\mathrm{24}{R}\:=\:{R}^{\mathrm{3}} \\ $$$$\:\mathrm{3}{R}^{\mathrm{2}} \:=\:\mathrm{24}{R} \\ $$$$\:{R}\:=\:\mathrm{8}\: \\ $$$$\:{ii}.\:\left({R}−{r}\right)^{\mathrm{2}} −{r}^{\mathrm{2}} =\:\left(\frac{{R}}{\:\sqrt{\mathrm{2}}}+{r}\right)^{\mathrm{2}} −\left(\frac{{R}}{\:\sqrt{\mathrm{2}}}−{r}\right)^{\mathrm{2}} \\ $$$$\:{R}^{\mathrm{2}} −\mathrm{2}{Rr}=\:\frac{\mathrm{4}{Rr}}{\:\mathrm{2}}\sqrt{\mathrm{2}} \\ $$$$\:{R}−\mathrm{2}{r}=\:\mathrm{2}{r}\sqrt{\mathrm{2}} \\ $$$$\:{R}\:=\:\mathrm{2}{r}\:+\:\mathrm{2}{r}\sqrt{\mathrm{2}} \\ $$$$\:{r}\:=\:\frac{{R}}{\mathrm{2}\:+\:\mathrm{2}\sqrt{\mathrm{2}}} \\ $$$$\:{r}\:=\:\frac{\mathrm{8}}{\mathrm{2}+\mathrm{2}\sqrt{\mathrm{2}}}\:=\:\frac{\mathrm{4}}{\mathrm{1}+\sqrt{\mathrm{2}}}\:=\:\frac{\mathrm{4}\left(\sqrt{\mathrm{2}}−\mathrm{1}\right)}{\mathrm{2}−\mathrm{1}}\:=\:\mathrm{4}\left(\sqrt{\mathrm{2}}−\mathrm{1}\right) \\ $$

Commented by normans last updated on 25/Feb/23

nice

$${nice} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com